Rare bird documentation form for Tundra Swan at Thomson Causeway, 1997 - McKay, Kellyet al (1997)
Rare bird documentation form for over two hundred Tundra Swans at Thomson Causeway in Carroll County, IL on December 27, 1997. Epson - sheet feed